AB1018 Articular Synovitis or Tenosynovitis - Which is More Involved toward Functional Disabilities in Patients with Rheumatoid Arthritis? Investigation of Wrist and Finger Joints by Ultrasound in Early-Stage Rheumatoid Arthritis. (10th June 2014) - Kawashiri, S.-Y.; Nishino, A.; Suzuki, T.; Horai, Y.; Nakashima, Y.; Iwamoto, N.; Ichinose, K.; Arima, K.; Tamai, M.; Nakamura, H.; Origuchi, T.; Aoyagi, K.; et al.
Abstract : Background: Both articular synovitis and tenosynovitis found by ultrasound (US) are representative findings in patients with rheumatoid arthritis (RA). These inflammatory changes appear to involve in functional disabilities of patients with RA, however, their precise correlations remain to be elucidated. Objectives: We have tried to investigate the role of articular synovitis and tenosynovitis of wrist and finger joints toward functional disabilities of patients with early-stage RA. Methods: Twenty RA patients, whose disease durations were less than 2 years with no obvious plain radiographic erosion at wrists and finger joints, were consecutively recruited. They gave their informed consent to be subjected to the protocol. Articular synovitis was assessed by US at the 22 joints including bilateral wrist joints, 1-5th metacarpophalangeal (MCP) joints, interphalangeal joints and 2nd - 5th proximal interphalangeal (PIP) joints. Flexor tenosynovitis was assessed at the 10 joints from bilateral 1-5th MCP joints. Articular synovitis as well as tenosynovitis of each joint were scored for gray scale (GS) and power Doppler (PD) in a semi-quantitative manner on the scale from 0 to 3. Functional disabilities of wrists and finger joints were assessed by the Grip-Health Assessment Questionnaire (HAQ) and visual analogue scale (VAS) (0-100 mm) of morning stiffness. The correlations of US variables with Grip-HAQ or morning stiffness-VAS were examined by Spearman's correlation coefficient test. Results: The median of disease durations was 4 months and that of DAS 28 was 4.47. Total sum of PD scores of articular synovitis from 22 joints, but not those of GS scores of articular synoviti as well as the GS and PD scores of tenosynovitis, significantly correlated with both the Grip-HAQ (r=0.55, p<0.01) and the morning stiffness-VAS (r=0.53, p<0.01). Regarding to individual sites, the sum of PD scores of articular synovitis in MCP joints, but not other sites, only significantly correlated with both the Grip-HAQ (r=0.56, p<0.01) and morning stiffness-VAS (r=0.53, p<0.01). Conclusions: The functional disabilities of wrists and finger joints are proved to be influenced mainly by PD-positive active articular synovitis, especially that of MCP joints in early-stage RA patients. References: Kawashiri SY, et al. Ultrasonographic examination of rheumatoid arthritis patients who are free of physical synovitis: power Doppler subclinical synovitis is associated with bone erosion. Rheumatology (Oxford). In press. Kawashiri SY, et al. The power Doppler ultrasonography score from 24 synovial sites or 6 simplified synovial sites, including the metacarpophalangeal joints, reflects the clinical disease activity and level of serum biomarkers in patients with rheumatoid arthritis. Rheumatology (Oxford) 2011; 50: 962-5. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4082